Energy confinement in the spherical tokamak Globus-M2 with a toroidal magnetic field reaching 0.8 T. (8th December 2021) - Kurskiev, G.S.; Gusev, V.K.; Sakharov, N.V.; Petrov, Yu.V.; Bakharev, N.N.; Balachenkov, I.M.; Bazhenov, A.N.; Chernyshev, F.V.; Khromov, N.A.; Kiselev, E.O.; Krikunov, S.V.; Minaev, V.B.; et al.
Abstract: The work presents the results of the energy confinement study carried out on the compact spherical tokamak Globus-M2 with a toroidal magnetic field as high as 0.8 T. A reproducible and stable discharge was obtained with the average plasma density (5–10) × 10 19  m −3 . Despite the increase in the magnetic field, the neutral beam injection (NBI) led to clear and reproducible transition to the H-mode accompanied by a decrease in the turbulence level at the plasma edge. NBI allowed effectively heat the plasma: electron and ion temperatures in the plasma core exceeded 1 keV. Compared to the previous experiments carried out with a toroidal magnetic field as high as 0.4 T plasma total stored energy was increased by a factor of 4. The main reason or this phenomenon is a strong dependence of the energy confinement time on the toroidal magnetic field in the spherical tokamak. It was experimentally confirmed that such kind of dependence is valid for ST with magnetic field up to 0.8 T. It has also been shown that the enhancement of the energy confinement in Globus-M2 with collisionality decrease is associated with an improvement of both electron and ion thermal insulation.